The Matrisome Genes From Hepatitis B–Related Hepatocellular Carcinoma Unveiled - Wei Chen; Romain Desert; Xiaodong Ge; Hui Han; Zhuolun Song; Sukanta Das; Dipti Athavale; Hong You; Natalia Nieto (Hepatology Communications, 2021)
Chronic hepatitis B virus (HBV) infection changes the composition of the extracellular matrix (ECM) and enables the onset and progression of hepatocellular carcinoma (HCC). The ensemble of ECM proteins and associated factors is a major component of the tumor microenvironment. Our aim was to unveil the matrisome genes from HBV‐related HCC. Transcriptomic and clinical profiles from 444 patients with HBV‐related HCC were retrieved from the Gene Expression Omnibus (GEO) and Cancer Genome Atlas (TCGA) repositories. Matrisome genes associated with HBV‐related hepatocarcinogenesis, matrisome gene modules, HCC subgroups, and liver‐specific matrisome genes were systematically analyzed, followed by identification of their biological function and clinical relevance. Eighty matrisome genes, functionally enriched in immune response, ECM remodeling, or cancer‐related pathways, were identified as associated with HBV‐related HCC, which could robustly discriminate HBV‐related HCC tumor from nontumor samples. Subsequently, four significant matrisome gene modules were identified as showing functional homogeneity linked to cell cycle activity. Two subgroups of patients with HBV‐related HCC were classified based on the highly correlated matrisome genes. The high‐expression subgroup (15.0% in the TCGA cohort and 17.9% in the GEO cohort) exhibited favorable clinical prognosis, activated metabolic activity, exhausted cell cycle, strong immune infiltration, and lower tumor purity. Four liver‐specific matrisome genes (F9, HPX [hemopexin], IGFALS [insulin‐like growth‐factor‐binding protein, acid labile subunit], and PLG [plasminogen]) were identified as involved in HBV‐related HCC progression and prognosis. Conclusion: This study identified the expression and function of matrisome genes from HBV‐related hepatocarcinogenesis, providing major insight to understand HBV‐related HCC and develop potential therapeutic opportunities.